Carbon microspheres as well as preparation method and application thereof

By forming a liquid metal layer on the carbon substrate and performing microwave plasma chemical vapor deposition treatment, carbon microspheres with sp2 and sp3 hybrid carbon were prepared, which solved the problems of insufficient conductivity and poor structural support in the application of a single hybrid carbon material, and realized the preparation of a multifunctional material.

CN119898750AActive Publication Date: 2025-04-29YONGJIANG LAB
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411952776.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-29
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

In practical applications, single hybrid carbon materials have problems such as insufficient conductivity, poor structural support, and unwell hardness and toughness, which are difficult to meet the comprehensive performance requirements.

Method used

Carbon microspheres with sp2 and sp3 hybrid carbon were formed by forming a liquid metal layer on the side of the carbon substrate and performing microwave plasma chemical vapor deposition treatment. The method includes two microwave plasma chemical vapor deposition treatments, the first treatment to etch the carbon substrate, the second treatment to form carbon microspheres, using hydrogen and methane as gas sources, and regulating the reaction conditions to control the structure and composition of the carbon microspheres.

Benefits of technology

The prepared carbon microspheres have both electrical conductivity, flexibility, and good thermal conductivity and hardness. They can regulate the content and crystal structure of sp3 hybrid carbon according to needs. They are suitable for battery electrode materials, cutting-edge semiconductor devices and medical contrast materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119898750A_ABST
    Figure CN119898750A_ABST
Patent Text Reader

Abstract

The invention discloses carbon microspheres as well as a preparation method and application thereof. The method for preparing the carbon microspheres comprises the following steps: forming a liquid metal layer on one side of a carbon substrate; performing first microwave plasma chemical vapor deposition treatment on one side, with the liquid metal layer, of the carbon substrate, and raising the temperature of the carbon substrate to an etching temperature to obtain a carbon substrate with an etching surface; a first gas source of the first microwave plasma chemical vapor deposition treatment comprises hydrogen, the etching temperature is higher than the evaporation temperature of the liquid metal layer, the etching temperature is higher than the decomposition temperature of the carbon substrate, and the decomposition temperature of the carbon substrate is higher than the evaporation temperature of the liquid metal layer; carrying out second microwave plasma chemical vapor deposition treatment on one side, with the etched surface, of the carbon substrate to obtain carbon microspheres; a second gas source for the second microwave plasma chemical vapor deposition treatment comprises hydrogen and methane. The carbon microspheres prepared by the preparation method disclosed by the invention comprise sp2 hybrid carbon and sp3 hybrid carbon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of micro-nano powder materials, and in particular, to carbon microspheres and preparation methods and applications thereof. Background Art

[0002] Due to its unique electronic structure, carbon atoms have a variety of hybrid states, mainly including sp 3 Hybridized carbon (such as diamond), sp 2 Hybrid carbon (such as graphene, fullerene, carbon nanotubes, etc.) and sp and sp 2 Hybridized hybrid orbital materials (such as graphyne), etc. These carbon materials in different hybrid states exhibit diverse chemical and physical properties, making carbon materials have wide application potential in many fields. However, single hybrid carbon materials are difficult to meet the growing comprehensive performance requirements.

[0003] It should be noted that the above statements are only used to provide background technical information related to the present application and do not necessarily constitute prior art. Summary of the invention

[0004] In the first aspect of the present application, the present application provides a method for preparing carbon microspheres, comprising: forming a liquid metal layer on one side of a carbon substrate; performing a first microwave plasma chemical vapor deposition treatment on the side of the carbon substrate having the liquid metal layer, so that the temperature of the carbon substrate is increased to the etching temperature to obtain the carbon substrate having an etched surface; the first gas source of the first microwave plasma chemical vapor deposition treatment includes hydrogen, the etching temperature is greater than the evaporation temperature of the liquid metal layer, the etching temperature is greater than the decomposition temperature of the carbon substrate, and the decomposition temperature of the carbon substrate is greater than the evaporation temperature of the liquid metal layer; performing a second microwave plasma chemical vapor deposition treatment on the side of the carbon substrate having the etched surface to obtain carbon microspheres; the second gas source of the second microwave plasma chemical vapor deposition treatment includes hydrogen and methane.

[0005] Therefore, the liquid metal layer can prevent the carbon substrate from being etched and nucleated prematurely, thereby reducing the risk of agglomerates forming on the surface of the carbon substrate and making the surface of the carbon substrate more inclined to form a single spherical structure. 3 The source of hybrid carbon, ionized methane gas can combine with the dangling bonds on the surface of the carbon substrate, promoting the sp 2 Hybridized carbon to sp 3 Hybridized carbon transforms to form sp 3 C-C bonds can then form secondary nuclei on the carbon substrate surface to form diamonds. 2 Hybridized carbon and sp 3Hybridized carbon.

[0006] In some embodiments, in the second gas source, the flow rate ratio of the methane to the hydrogen is (0-15):100. 3 The source of hybrid carbon can be adjusted by adjusting the amount of methane. 3 The content and crystal structure of hybrid carbon.

[0007] In some embodiments, the liquid metal layer includes at least one of metal gallium, gallium-iron alloy, gallium-magnesium alloy, gallium-nickel alloy, gallium-iron-nickel alloy, gallium-zinc alloy, gallium-magnesium-zinc alloy, gallium-indium alloy, gallium-tin alloy, and gallium-indium-tin alloy. Therefore, metal gallium and gallium-based alloys are suitable for the method for preparing carbon microspheres in this application.

[0008] In some embodiments, the carbon substrate includes at least one of graphite and glassy carbon. Therefore, selecting a carbon substrate of a suitable material as a reaction substrate not only provides a stable platform for the growth of carbon microspheres, but also is a sp 2 The source of hybrid carbon.

[0009] In some embodiments, the formation of the liquid metal layer on one side of the carbon substrate satisfies at least one of the following conditions: the surface temperature of the carbon substrate is 21°C-25°C; the surface relative humidity of the carbon substrate is less than or equal to 65%. Therefore, the surface temperature and surface relative humidity of the carbon substrate need to be strictly controlled to form a liquid metal layer on the surface of the carbon substrate.

[0010] In some embodiments, the etching temperature is 800° C.-850° C. Thus, by selecting a suitable etching temperature, the carbon substrate can be effectively etched while reducing the risk of over-etching.

[0011] In some embodiments, the second microwave plasma chemical vapor deposition process satisfies at least one of the following conditions: the microwave power of the second microwave plasma chemical vapor deposition process is 3600W-4600W; the reaction time of the second microwave plasma chemical vapor deposition process is 30min-90min; the working pressure of the second microwave plasma chemical vapor deposition process is 17.3KPa-20KPa; in the second microwave plasma chemical vapor deposition process, the temperature of the side of the carbon substrate having the etched surface is 900℃-1100℃. Thus, by controlling the parameters of the second microwave plasma chemical vapor deposition process, the sp in the carbon microspheres can be regulated. 2 Hybridized carbon and sp 3 The proportion of hybridized carbon, and sp 3 The form of hybrid carbon.

[0012] In a second aspect of the present application, the present application provides a carbon microsphere prepared by the above method, wherein the carbon microsphere comprises sp 2 Hybridized carbon and sp 3 Hybridized carbon. Therefore, the carbon microspheres of the present application have both electrical conductivity and flexibility, as well as good thermal conductivity and hardness.

[0013] In some embodiments, the particle size of the carbon microspheres is 5 μm-300 μm. Therefore, the carbon microspheres of the present application have a large particle size range, and the particle size of the carbon microspheres can be adjusted according to actual needs.

[0014] In some embodiments, the sp 3 Hybridized carbon includes at least one of amorphous diamond and polycrystalline diamond. 3 Types of hybrid carbon.

[0015] In some embodiments, the sp 2 Hybrid carbon includes graphite.

[0016] In the third aspect of the present application, the present application provides the use of the carbon microspheres obtained by the preparation method of the first aspect of the present application and the carbon microspheres of the second aspect of the present application in battery electrode materials, cutting-edge semiconductor devices or human-affinity medical imaging materials. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:

[0018] Figure 1 It is a schematic diagram of a method for preparing carbon microspheres in one embodiment of the present application.

[0019] Figure 2 The coating effect of liquid metal gallium under different temperature conditions, among which, Figure 2 Figure a shows the coating effect at 24.3°C and 57% relative humidity. Figure 2 Figure b shows the coating effect at 27°C; Figure 2 Figure c shows the coating effect at 19°C.

[0020] Figure 3 This is a characterization result diagram of carbon microspheres in Example 1, wherein: Figure 3 Figure a in the figure is a scanning electron microscope image of a single carbon microsphere; Figure 3 Figure b is the Raman spectrum of carbon microspheres. Figure 3 Figure c is a nanoforce platform test curve of a single carbon microsphere.

[0021] Figure 4This is a characterization result diagram of carbon microspheres in Example 2, wherein: Figure 4 Figure a in the figure is a scanning electron microscope image of a single carbon microsphere; Figure 4 Figure b is the Raman spectrum of carbon microspheres.

[0022] Figure 5 This is a characterization result diagram of carbon microspheres in Example 3, wherein: Figure 5 Figure a in the figure is a scanning electron microscope image of a single carbon microsphere; Figure 5 Figure b is the Raman spectrum of carbon microspheres.

[0023] Figure 6 This is a characterization result diagram of carbon microspheres in Example 4, wherein: Figure 6 Figure a in the figure is a scanning electron microscope image of a single carbon microsphere; Figure 6 Figure b is the Raman spectrum of carbon microspheres.

[0024] Figure 7 This is a characterization result diagram of carbon microspheres in Comparative Example 1, wherein: Figure 7 Figure a is a scanning electron microscope image of carbon microsphere clusters; Figure 7 Figure b is the Raman spectrum of carbon microspheres. DETAILED DESCRIPTION

[0025] Hereinafter, the carbon microspheres of the present application, their preparation methods and application embodiments are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.

[0026] " Scope " disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be to include end values ​​or not include end values, and can be combined arbitrarily, that is, any lower limit can form a scope with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for a particular parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 listed, and if the maximum range values ​​3,4 and 5 are listed, the following scope can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0027] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0029] Unless otherwise defined, all technical and scientific terms used in this application have the same meanings as those commonly understood by technicians in the technical field to which this application belongs; the terms used in this application are only for the purpose of describing specific embodiments and are not intended to limit this application; unless otherwise specified, the numerical values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (for example, they can be tested according to the methods given in the embodiments of this application).

[0030] In the description of this application, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. "First feature" and "second feature" may include one or more of the features.

[0031] In the description of the present application, "A and / or B" may include the case of A alone, the case of B alone, or any of the cases of A and B, where A and B are only used for examples and may be any technical feature connected by "and / or" in the present application.

[0032] Single hybrid carbon materials have obvious limitations in practical applications. For example, in the field of silicon-carbon negative electrode materials for lithium-ion batteries, sp 2 Although hybrid carbon materials have good electrical conductivity, they lack sufficient structural support and are unable to withstand the volume expansion of silicon particles, which may lead to the rupture of the negative electrode material. 3 Although hybrid diamond has high hardness, its conductivity is poor, and diamond is too rigid and lacks toughness, so it is easy to break during use. Therefore, it is particularly important to develop carbon materials with multiple hybrid states to overcome the limitations of single hybrid carbon materials.

[0033] In the first aspect of the present application, the present application provides a method for preparing carbon microspheres, referring to Figure 1 , the method comprising:

[0034] S100, forming a liquid metal layer on one side of the carbon substrate.

[0035] Liquid metal generally refers to a metal or alloy that is liquid at room temperature, that is, the liquid metal used in the present application has a relatively low melting point, so the liquid metal has good fluidity at room temperature, and the liquid metal can flow on the surface of the carbon substrate to form a liquid metal layer.

[0036] In some embodiments, the liquid metal layer includes at least one of metal gallium, gallium-iron alloy, gallium-magnesium alloy, gallium-nickel alloy, gallium-iron-nickel alloy, gallium-zinc alloy, gallium-magnesium-zinc alloy, gallium-indium alloy, gallium-tin alloy, and gallium-indium-tin alloy. Therefore, metal gallium and gallium-based alloys are suitable for the method for preparing carbon microspheres in the present application.

[0037] In some embodiments, the carbon substrate includes at least one of graphite and glassy carbon. Therefore, selecting a carbon substrate of a suitable material as a reaction substrate not only provides a stable platform for the growth of carbon microspheres, but also is a good choice for the growth of carbon microspheres. 2 The source of hybrid carbon.

[0038] In some embodiments, the carbon substrate has a carbon content greater than or equal to 99.99%.

[0039] As examples, the carbon content of the carbon substrate includes, but is not limited to, 99.99%, 99.999%, 99.9999%, or 100%.

[0040] In some embodiments, the surface of the carbon substrate is subjected to mechanical polishing, thereby improving the flatness and smoothness of the surface of the carbon substrate. The smooth and flat carbon substrate can improve the fluidity of the liquid metal and help form a uniform liquid metal layer.

[0041] In some embodiments, the formation of the liquid metal layer on one side of the carbon substrate satisfies at least one of the following conditions: the surface temperature of the carbon substrate is 21° C.-25° C.; the surface relative humidity of the carbon substrate is less than or equal to 65%.

[0042] In the process of forming the liquid metal layer, the surface temperature and relative humidity of the carbon substrate need to be strictly controlled. This is because at higher temperatures, liquid metal exhibits higher fluidity and surface energy, resulting in a larger wetting angle between the liquid metal and the surface of the carbon substrate, which makes it difficult for the liquid metal to be evenly distributed on the surface of the carbon substrate; at lower temperatures, the liquid metal solidifies too quickly, resulting in uneven agglomerations on the surface of the carbon substrate. Controlling the relative humidity of the carbon substrate helps reduce the hydration between the liquid metal layer and water molecules to improve the stability of the liquid metal layer.

[0043] Taking the liquid metal as gallium and the carbon substrate as graphite as an example, the graphite surface is coated with liquid gallium at a temperature of 24.3°C and a relative humidity of 57%. The coating effect is as follows: Figure 2 As shown in Figure c, a liquid metal layer is formed on the graphite surface; when the temperature rises to 27°C, the coating effect is as follows Figure 2 As shown in Figure a, liquid metal gallium gathers into water droplets on the graphite surface, and it is difficult for metal gallium to be coated on the graphite surface; when the temperature is reduced to 19°C, the coating effect is as follows Figure 2 As shown in Figure b, the liquid metal gallium condenses the moment it contacts the graphite surface, causing agglomerates to form on the graphite surface, affecting the coating effect.

[0044] As an example, the surface temperature of the carbon substrate may be 21°C, 21.5°C, 22°C, 22.5°C, 23°C, 23.5°C, 24°C, 24.5°C, or 25°C.

[0045] As examples, the relative humidity of the surface of the carbon substrate includes, but is not limited to, 0%, 15%, 30%, 45%, 60% or 65%.

[0046] In some embodiments, the liquid metal layer is formed on one side of the carbon substrate and the following conditions are met simultaneously: the surface temperature of the carbon substrate is 21° C.-25° C.; and the surface relative humidity of the carbon substrate is less than or equal to 65%.

[0047] S200, performing a first microwave plasma chemical vapor deposition treatment on a side of the carbon substrate having the liquid metal layer, so that the temperature of the carbon substrate is increased to an etching temperature to obtain a carbon substrate having an etched surface; the first gas source of the first microwave plasma chemical vapor deposition treatment includes hydrogen, the etching temperature is greater than the evaporation temperature of the liquid metal layer, the etching temperature is greater than the decomposition temperature of the carbon substrate, and the decomposition temperature of the carbon substrate is greater than the evaporation temperature of the liquid metal layer.

[0048] The working principle of microwave plasma chemical vapor deposition (MPCVD) is to generate microwaves through a microwave source, which enter the reaction chamber after being coupled through a waveguide and a mode converter. Under the action of the microwave electromagnetic field, hydrogen is excited into a plasma state. Plasma is an ionized gas-like substance composed of positive and negative ions produced after atoms and atomic groups are ionized after some electrons are deprived. The plasma is formed on the carbon substrate in a spherical or ellipsoidal shape, and the high temperature of the plasma can be used to heat the carbon substrate to the etching temperature. In the present application, in the process of heating the carbon substrate to the etching temperature, the temperature first reaches the evaporation temperature of the liquid metal layer, at which time the liquid metal layer is quickly removed by evaporation; then the temperature reaches the decomposition temperature of the carbon substrate, at which time the carbon substrate is etched by hydrogen.

[0049] Therefore, during the plasma ignition and carbon substrate heating process, the liquid metal layer is used to isolate hydrogen and the carbon substrate to protect the carbon substrate; when the carbon substrate is heated to the evaporation temperature of the liquid metal layer, it is quickly removed, and hydrogen begins to etch the carbon substrate. At the same time, the high-temperature covalent bond structure of the liquid metal is conducive to catalyzing the conversion of CH bonds to CC bonds, thereby forming a uniform spherical carbon nucleus on the surface of the carbon substrate. As a result, the liquid metal layer can prevent the carbon substrate from being etched and nucleated prematurely, thereby reducing the risk of agglomerates forming on the surface of the carbon substrate, making the surface of the carbon substrate more inclined to form a single spherical structure.

[0050] In some embodiments, the etching temperature is 800° C.-850° C. Thus, by selecting a suitable etching temperature, the carbon substrate can be effectively etched while reducing the risk of over-etching.

[0051] As an example, the etching temperature may be 800°C, 805°C, 810°C, 815°C, 820°C, 825°C, 830°C, 835°C, 840°C, 845°C, or 850°C.

[0052] In some embodiments, the purity of the hydrogen is greater than or equal to 99.99%.

[0053] As an example, the purity of hydrogen includes, but is not limited to, 99.99%, 99.999%, 99.9999%, or 100%.

[0054] S300, performing a second microwave plasma chemical vapor deposition process on the side of the carbon substrate having the etched surface to obtain carbon microspheres; the second gas source of the second microwave plasma chemical vapor deposition process includes hydrogen and methane.

[0055] The surface of the carbon substrate etched by hydrogen produces dangling bonds, and methane acts as sp 3 The source of hybrid carbon, ionized methane gas can combine with the dangling bonds on the surface of the carbon substrate, promoting the sp 2 Hybridized carbon to sp 3Hybridized carbon transforms to form sp 3 C-C bonds can then form secondary nucleation on the carbon substrate surface to form diamond.

[0056] sp 2 Hybridized carbon to sp 3 Hybridized carbon transforms to form sp 3 The process of forming a CC bond requires energy, which allows the carbon atom to overcome the energy barrier and form a sp 3 Hybrid diamond structure. Therefore, the sp 2 Hybridized carbon and sp 3 The proportion of hybrid carbon

[0057] The diamond formed on the surface of the carbon substrate exists in an amorphous state at first. As the energy increases, the amorphous carbon can be transformed into orderly arranged carbon atoms. These orderly arranged carbon atoms serve as seed crystals, which gradually grow and tend to grow first. <111> The diamond flakes grow gradually, and through the mutual compression and combination between the grains, a polycrystalline diamond with a continuous staggered structure is formed.

[0058] In some embodiments, in the second gas source, the flow rate ratio of methane to hydrogen is (0-15):100. Thus, methane is used as sp 3 The source of hybrid carbon can be adjusted by adjusting the amount of methane. 3 The content and crystal structure of hybrid carbon.

[0059] As an example, the flow rate ratio of methane to hydrogen may be 0:100, 1:100, 2:100, 3:100, 4:100, 5:100, 6:100, 7:100, 8:100, 9:100, 10:100, 11:100, 12:100, 13:100, 14:100, or 15:100.

[0060] Under the action of hydrogen etching, the carbon substrate generates dangling bonds and free hydrocarbons or carbon ions. When the flow rate ratio of methane to hydrogen is 0:100, that is, when no methane is introduced, the dangling bonds and free hydrocarbons or carbon ions are combined again, and the carbon atoms are rearranged to form sp 3 Hybridized carbon; but forms sp 3 During the process of hybridization of carbon, its growth mode changes from normal layered growth and hillock growth to irregular growth. This irregular growth causes carbon atoms to aggregate to form polycrystalline diamond, which is characterized by an uneven crystal structure and an irregular shape with sharp edges and corners. In addition to forming sp 3 In addition to the hybrid carbon, some sp 2Hybridized carbon, therefore, carbon microspheres have sp 2 Hybridized carbon and sp 3 Hybridized carbon.

[0061] In some embodiments, the purity of hydrogen and / or methane is greater than or equal to 99.99%.

[0062] As examples, the purity of hydrogen and / or methane includes, but is not limited to, 99.99%, 99.999%, 99.9999%, or 100%.

[0063] In some embodiments, the second microwave plasma chemical vapor deposition process satisfies at least one of the following conditions: the microwave power of the second microwave plasma chemical vapor deposition process is 3600W-4600W; the reaction time of the second microwave plasma chemical vapor deposition process is 30min-90min; the working pressure of the second microwave plasma chemical vapor deposition process is 17.3KPa-20KPa; in the second microwave plasma chemical vapor deposition process, the temperature of the side of the carbon substrate having the etched surface is 900℃-1100℃. Thus, by controlling the parameters of the second microwave plasma chemical vapor deposition process, the sp in the carbon microspheres can be regulated. 2 Hybridized carbon and sp 3 The proportion of hybridized carbon, and sp 3 The form of hybrid carbon.

[0064] As an example, the microwave power of the second microwave plasma chemical vapor deposition process may be 3600 W, 3700 W, 3800 W, 3900 W, 4000 W, 4100 W, 4200 W, 4300 W, 4400 W, 4500 W, or 4600 W.

[0065] As an example, the reaction time of the second microwave plasma chemical vapor deposition process may be 30 min, 40 min, 50 min, 60 min, 70 min, 80 min or 90 min.

[0066] As an example, the working pressure of the second microwave plasma chemical vapor deposition process may be 17.3 KPa, 17.6 KPa, 17.9 KPa, 18.2 KPa, 18.5 KPa, 18.8 KPa, 19.1 KPa, 19.4 KPa, 19.7 KPa or 20 KPa.

[0067] As an example, the temperature of the side of the carbon substrate having the etched surface may be 900°C, 920°C, 940°C, 960°C, 980°C, 1000°C, 1020°C, 1040°C, 1060°C, 1080°C or 1100°C.

[0068] In some embodiments, the second microwave plasma chemical vapor deposition treatment satisfies the following conditions at the same time: the microwave power of the second microwave plasma chemical vapor deposition treatment is 3600W-4600W; the reaction time of the second microwave plasma chemical vapor deposition treatment is 30min-90min; the working pressure of the second microwave plasma chemical vapor deposition treatment is 17.3KPa-20KPa; in the second microwave plasma chemical vapor deposition treatment, the temperature of the side of the carbon substrate with the etched surface is 900℃-1100℃.

[0069] In a second aspect of the present application, the present application provides a carbon microsphere prepared by the above method, the carbon microsphere comprising sp 2 Hybridized carbon and sp 3 Hybridized carbon. Therefore, the carbon microspheres of the present application have both electrical conductivity and flexibility, as well as good thermal conductivity and hardness.

[0070] In some embodiments, the particle size of the carbon microspheres is 5 μm-300 μm. Therefore, the carbon microspheres of the present application have a large particle size range, and the particle size of the carbon microspheres can be adjusted according to actual needs.

[0071] As an example, the particle size of the carbon microspheres can be 5 μm, 10 μm, 20 μm, 40 μm, 60 μm, 80 μm, 100 μm, 120 μm, 140 μm, 160 μm, 180 μm, 200 μm, 220 μm, 240 μm, 260 μm, 280 μm or 300 μm.

[0072] In some embodiments, sp 3 Hybridized carbon includes at least one of amorphous diamond and polycrystalline diamond. 3 Types of hybrid carbon.

[0073] In some embodiments, sp 2 Hybrid carbon includes graphite.

[0074] In the third aspect of the present application, the present application provides the use of the carbon microspheres obtained by the preparation method of the first aspect of the present application and the carbon microspheres of the second aspect of the present application in battery electrode materials, cutting-edge semiconductor devices or human-affinity medical imaging materials.

[0075] The scheme of the present application is described below by specific examples. It should be noted that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If no specific technology or conditions are specified in the examples, the technology or conditions described in the literature in this area or the product instructions are used. The reagents or instruments used are not specified by the manufacturer, and are all conventional products that can be obtained commercially.

[0076] Example 1

[0077] The preparation of carbon microspheres comprises the following steps:

[0078] S100, taking a graphite sheet with a carbon content of 99.999%, and mechanically polishing the surface of the graphite sheet; then placing the polished graphite sheet in an environment with a temperature of 24.3° C. and a relative humidity of 57%, and after a period of time to make the temperature and relative humidity of the graphite sheet consistent with those of the environment, coating the surface of the graphite sheet with liquid metal gallium; the liquid metal gallium flows on the surface of the graphite sheet to form a uniform liquid metal layer on the surface of the graphite sheet.

[0079] S200, placing a graphite sheet with a liquid metal layer in an MPCVD reaction chamber, introducing hydrogen with a purity of 99.999% into the reaction chamber, causing plasma to glow in a hydrogen atmosphere, and performing a temperature increase operation while maintaining a ratio of working pressure to microwave power of 0.6 KPa / 100 W; when the temperature rises to 750°C, the liquid metal gallium is completely evaporated and removed; when the temperature continues to rise to 800°C, the surface of the graphite sheet is etched by hydrogen to produce free hydrocarbons or carbon ions, causing the plasma to change from pink to white.

[0080] S300, introducing methane with a purity of 99.999% into the reaction chamber, and controlling the flow rate ratio of methane to hydrogen to be 1:10; at the same time, increasing the microwave power of the reaction chamber to 3600W, the working pressure to 18KPa, and the surface temperature of the graphite sheet to 912°C, and obtaining carbon microspheres after 1 hour of deposition treatment. After stopping the introduction of methane, during the process of shutting down the plasma, hydrogen etches the connection points between the carbon microspheres and the graphite sheet, so that the carbon microspheres can be separated from the surface of the graphite sheet by simple vibration treatment.

[0081] Example 2

[0082] The difference between Example 2 and Example 1 is that:

[0083] S300, increase the microwave power of the reaction chamber to 3800W, the working pressure to 18.3KPa, and the surface temperature of the graphite sheet to 1005℃.

[0084] Example 3

[0085] The difference between Example 3 and Example 1 is that:

[0086] S300, increase the microwave power of the reaction chamber to 4200W, the working pressure to 19KPa, and the surface temperature of the graphite sheet to 1100℃.

[0087] Example 4

[0088] The difference between Example 4 and Example 1 is that methane is not introduced into the reaction chamber.

[0089] Comparative Example 1

[0090] The difference between Comparative Example 1 and Example 1 is that the surface of the graphite sheet is not coated with liquid metal gallium.

[0091] Structural characterization

[0092] 1. The carbon microspheres obtained in Examples 1 to 4 and Comparative Example 1 were scanned by electron microscope, and the testing instrument model was Hitachi / Regulus 8230.

[0093] 2. The separated carbon microspheres of Examples 1 to 4 and Comparative Example 1 were uniformly dispersed in ethanol, and then the ethanol solution containing the carbon microspheres was drop-casted on the surface of a stainless steel substrate for Raman spectroscopy testing. The testing instrument model was HORIBA / LabRAM Odyssey, and the excitation light source wavelength was 532 nm.

[0094] The characterization results of the carbon microspheres in Example 1 are as follows Figure 3 As shown, Figure 3 Figure a is a scanning electron microscope image of a single carbon microsphere. Figure 3 Figure b in the figure is the Raman spectrum of carbon microspheres. Figure 3 As shown in Figure a, the sphericity of a single carbon microsphere is high, the surface is smooth, and the particle size of a single sphere is 5.1 μm. Figure 3 As shown in Figure b, 1348.2cm -1 There is an obvious D peak at 1581.3cm -1 There is an obvious graphite phase G peak at 2695.1cm -1 There is an obvious G' peak at , indicating that the carbon microspheres have a graphene-like layered structure at the nanoscale and have good electrical conductivity. In addition, the single carbon microsphere of Example 1 was tested by a nanoforce platform, and the nanoforce platform test curve is shown in Figure 3 As shown in Figure c, the red line records the displacement (s) change of the indenter, and the black line records the force (F) curve measured by the indenter. From the red line, it can be seen that the indenter is controlled to press down 8μm, which is larger than the particle size of the single ball 5.1μm, which shows that the hardness of the single ball particle is strong, causing the tungsten steel indenter to undergo elastic deformation; and the force curve shows that under the extreme pressure (90mN) of the nanoforce platform detector, the single ball particle is not broken and deformed, while the high-purity graphite particles of the same size will break when the device applies a force of less than 20mN, which shows that the single carbon microsphere of Example 1 has mechanical properties far superior to those of high-purity graphite particles, because the carbon microspheres of Example 1 have non-crystalline diamonds.

[0095] The characterization results of the carbon microspheres in Example 2 are as follows Figure 4 As shown, Figure 4 Figure a is a scanning electron microscope image of a single carbon microsphere. Figure 4 Figure b in the figure is the Raman spectrum of carbon microspheres. Figure 4 As shown in Figure a, the sphericity of the single carbon microsphere is high, a white diamond sheet structure appears on the surface of the single ball, and the particle size of the single ball is 9.7μm. Figure 4 As shown in Figure b, 1330.8cm -1 There is a diamond signal peak at 3 Hybrid diamond; 1568cm -1 The G peak of the graphite phase is present at the position of the carbon microspheres and is shifted and broadened as a whole, indicating that a large number of sp 2 Hybrid graphite phase; 2700cm -1 The G' peak disappears, indicating that the carbon microspheres have lost their graphene-like multilayer structure, and theoretically the conductivity will decrease.

[0096] The characterization results of the carbon microspheres in Example 3 are as follows Figure 5 As shown, Figure 5 Figure a is a scanning electron microscope image of a single carbon microsphere. Figure 5 Figure b in the figure is the Raman spectrum of carbon microspheres. Figure 5 As shown in Figure a, the sphericity of a single carbon microsphere is high, and a continuous staggered diamond crystal structure appears on the surface of the single sphere. The particle size of the single sphere is 45.2μm. Figure 5 As shown in Figure b, 1332.1cm -1 There is a standard sp 3 Hybrid diamond signal peak; 1580cm -1 The graphite phase G peak at 1450 cm -1 -1650cm -1 The hump indicates that the sp 2 The hybrid graphite phase component is further reduced; at the same time, 2700cm -1 The G' peak disappears, indicating that the carbon microspheres have lost their graphene-like multilayer structure, and theoretically the conductivity will decrease.

[0097] The characterization results of the carbon microspheres in Example 4 are as follows Figure 6 As shown, Figure 6 Figure a is a scanning electron microscope image of a single carbon microsphere. Figure 6 Figure b in the figure is the Raman spectrum of carbon microspheres. Figure 6 As shown in Figure a, the sphericity of the single carbon microsphere is poor, and it has a polycrystalline diamond crystal structure with sharp edges and irregular shapes. Figure 6 As shown in Figure b, 1332.1cm -1 There is a standard sp 3Hybrid diamond signal peak, 1580cm -1 The graphite phase G peak at 10 indicates that there are still a lot of sp 2 Hybrid graphite phase carbon.

[0098] The characterization results of the carbon microspheres in Comparative Example 1 are as follows Figure 7 As shown, Figure 7 Figure a is a scanning electron microscope image of carbon microsphere clusters. Figure 7 Figure b in the figure is the Raman spectrum of carbon microspheres. Figure 7 As shown in Figure a, the carbon microspheres have obvious cluster structures, and the cluster particle size cannot be accurately measured. The size of the cluster particles is much larger than the single carbon microsphere size of Example 1, which indicates that when liquid metal gallium is not coated, the surface of the graphite sheet has uneven nucleation, and it is difficult to generate uniformly dispersed single spheres. Figure 7 As shown in Figure b, 1332.1cm -1 There is a standard sp 3 Hybrid diamond signal peak, 1580cm -1 The graphite phase G peak at 10 indicates that there are still a lot of sp 2 Hybrid graphite phase carbon; 1348.6cm -1 There is an obvious D peak at 1581.3cm -1 There is an obvious sp 2 The graphite phase G peak and 2695.1cm -1 There is a strong G' peak at

[0099] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing carbon microspheres, characterized in that: include: forming a liquid metal layer on one side of the carbon substrate; Performing a first microwave plasma chemical vapor deposition process on the side of the carbon substrate having the liquid metal layer, so that the temperature of the carbon substrate is raised to an etching temperature, so as to obtain the carbon substrate having an etched surface; The first gas source of the first microwave plasma chemical vapor deposition process includes hydrogen, the etching temperature is greater than the evaporation temperature of the liquid metal layer, the etching temperature is greater than the decomposition temperature of the carbon substrate, and the decomposition temperature of the carbon substrate is greater than the evaporation temperature of the liquid metal layer; A second microwave plasma chemical vapor deposition treatment is performed on the side of the carbon substrate having the etched surface to obtain carbon microspheres; a second gas source of the second microwave plasma chemical vapor deposition treatment includes hydrogen and methane.

2. The method according to claim 1, characterized in that In the second gas source, the flow rate ratio of the methane to the hydrogen is (0-15):

100.

3. The method according to claim 1, characterized in that The liquid metal layer comprises at least one of metal gallium, gallium-iron alloy, gallium-magnesium alloy, gallium-nickel alloy, gallium-iron-nickel alloy, gallium-zinc alloy, gallium-magnesium-zinc alloy, gallium-indium alloy, gallium-tin alloy and gallium-indium-tin alloy; and / or, The carbon substrate includes at least one of graphite and glassy carbon.

4. The method according to any one of claims 1 to 3, characterized in that: The formation of the liquid metal layer on one side of the carbon substrate satisfies at least one of the following conditions: The surface temperature of the carbon substrate is 21°C-25°C; The surface relative humidity of the carbon substrate is less than or equal to 65%.

5. The method according to any one of claims 1 to 3, characterized in that: The etching temperature is 800°C-850°C.

6. The method according to any one of claims 1 to 3, characterized in that: The second microwave plasma chemical vapor deposition process satisfies at least one of the following conditions: The microwave power of the second microwave plasma chemical vapor deposition process is 3600W-4600W; The reaction time of the second microwave plasma chemical vapor deposition treatment is 30min-90min; The working pressure of the second microwave plasma chemical vapor deposition process is 17.3KPa-20KPa; In the second microwave plasma chemical vapor deposition process, the temperature of the carbon substrate having the etched surface is 900° C.-1100° C.

7. A carbon microsphere, characterized in that: Prepared by the method according to any one of claims 1 to 6, the carbon microspheres include sp 2 Hybridized carbon and sp 3 Hybridized carbon.

8. The carbon microspheres according to claim 7, characterized in that The particle size of the carbon microspheres is 5 μm-300 μm.

9. The carbon microspheres according to claim 7, characterized in that: The sp 3 The hybrid carbon includes at least one of amorphous diamond and polycrystalline diamond; and / or, The sp 2 Hybrid carbon includes graphite.

10. Use of the carbon microspheres as claimed in any one of claims 7 to 9, or the carbon microspheres prepared by the method as claimed in any one of claims 1 to 8 in battery electrode materials, cutting-edge semiconductor devices or human-friendly medical imaging materials.

Citation Information

Patent Citations

  • Method for rapidly preparing CVD diamond at constant temperature

    CN116240626A

  • Graphene-diamond composite coating as well as preparation method and application thereof

    CN118996371A

  • Method of forming a layer formed with poly- or single-crystal diamond

    DE102017205417A1

  • Method of toughening diamond coated tools

    US4988421A

  • Processing system and method for chemical vapor deposition of a metal layer using a liquid precursor

    US6409837B1